ORGANIZATION OF THE FORMATION OF HISTORICAL THINKING OF SCHOOLCHILDREN IN AN EDUCATIONAL ORGANIZATION (Ta'limning zamonaviy transformatsiyasi, 2024)
The article deals with theoretical approaches to the formation of historical thinking among schoolchildren in a general educational organization.The article discusses theoretical approaches to the formation of historical thinking among schoolchildren in general education organizations.